Distinct Patterns of Blood Cytokines Beyond a Cytokine Storm Predict Mortality in COVID-19 - Herr C; Mang S; Mozafari B; Guenther K; Speer T; Seibert M; Srikakulam SK; Beisswenger C; Ritzmann F; Keller A; Mueller R; Smola S; et al. (Dove Medical Press, 2021)
Christian Herr,1 Sebastian Mang,1 Bahareh Mozafari,1 Katharina Guenther,1 Thimoteus Speer,2 Martina Seibert,1 Sanjay Kumar Srikakulam,1 Christoph Beisswenger,1 Felix Ritzmann,1 Andreas Keller,3 Rolf Mueller,4 Sigrun Smola,5 Dominic Eisinger,6 Michael Zemlin,7 Guy Danziger,1 Thomas Volk,8 Sabrina Hoersch,8 Marcin Krawczyk,9 Frank Lammert,9 Thomas Adams,9 Gudrun Wagenpfeil,10 Michael Kindermann,11 Constantin Marcu,11 Zuhair Wolf Dietrich Ataya,12 Marc Mittag,13 Konrad Schwarzkopf,13 Florian Custodis,13 Daniel Grandt,13 Harald Schaefer,14 Kai Eltges,14 Philipp M Lepper,1 Robert Bals1 On behalf of the CORSAAR Study Group1Department of Internal Medicine V - Pulmonology, Allergology and Critical Care Medicine, Saarland University, Homburg, 66421, Germany; 2Department of Internal Medicine IV - Nephrology and Hypertension & Translational Cardio-Renal Medicine, Saarland University, Homburg, 66421, Germany; 3Clinical Bioinformatics, Saarland University, Homburg, 66421, Germany; 4Helmholtz-Institute for Pharmaceutical Science Saarland, Saarbrücken, 66123, Germany; 5Institute for Virology, Saarland University, Homburg, 66421, Germany; 6Myriad RBM Inc., Austin, TX, 78759, USA; 7Department of General Pediatrics and Neonatology, Saarland University, Homburg, 66421, Germany; 8Department of Anesthesiology, Intensive Care Medicine and Pain Therapy, Saarland University, Homburg, 66421, Germany; 9Department of Internal Medicine II - Gastroenterology, Saarland University, Homburg, 66421, Germany; 10Institute for Medical Biometry, Epidemiology and Medical Informatics, Saarland University, Homburg, 66421, Germany; 11Department of Internal Medicine, Cardiology and Intensive Care Medicine, Caritas Hospital St. Theresia Saarbrücken, Saarbrücken, 66113, Germany; 12Department of Gastroenterology, Internal and Intensive Care Medicine, Caritas Hospital St. Josef Saarbrücken, Saarbrücken, 66125, Germany; 13Department of Anesthesiology, Gastroenterology and Intensive Care Medicine, Saarbrücken Hospital, Saarbrücken, 66119, Germany; 14Department of Internal Medicine and Pulmonology, SHG-Hospital Völklingen, Saarbrücken, 66333, GermanyCorrespondence: Robert BalsDepartment of Internal Medicine V - Pulmonology, Allergology and Critical Care Medicine, Saarland University, Homburg, 66421, GermanyTel +49 6841 16 15051Email robert.bals@uks.euBackground: COVID-19 comprises several severity stages ranging from oligosymptomatic disease to multi-organ failure and fatal outcomes. The mechanisms why COVID-19 is a mild disease in some patients and progresses to a severe multi-organ and often fatal disease with respiratory failure are not known. Biomarkers that predict the course of disease are urgently needed. The aim of this study was to evaluate a large spectrum of established laboratory measurements.Patients and Methods: Patients from the prospective PULMPOHOM and CORSAAR studies were recruited and comprised 35 patients with COVID-19, 23 with conventional pneumonia, and 28 control patients undergoing elective non-pulmonary surgery. Venous blood was used to measure the serum concentrations of 79 proteins by Luminex multiplex immunoassay technology. Distribution of biomarkers between groups and association with disease severity and outcomes were analyzed.Results: The biomarker profiles between the three groups differed significantly with elevation of specific proteins specific for the respective conditions. Several biomarkers correlated significantly with disease severity and death. Uniform manifold approximation and projection (UMAP) analysis revealed a significant separation of the three disease groups and separated between survivors and deceased patients. Different models were developed to predict mortality based on the baseline measurements of several protein markers. A score combining IL-1ra, IL-8, IL-10, MCP-1, SCF and CA-9 was associated with significantly higher mortality (AUC 0.929).Discussion: Several newly identified blood markers were significantly increased in patients with severe COVID-19 (AAT, EN-RAGE, myoglobin, SAP, TIMP-1, vWF, decorin) or in patients that died (IL-1ra, IL-8, IL-10, MCP-1, SCF, CA-9). The use of established assay technologies allows for rapid translation into clinical practice.Keywords: biomarker, inflammation, SARS-CoV2